Stock Returns, Dividend Yields, and Taxes - Naranjo, Andy; Nimalendran, M.; Ryngaert, Mike (Journal of Finance, 1998)
Using an improved measure of a common stock's annualized dividend yield, we document that risk‐adjusted NYSE stock returns increase in dividend yield during the period from 1963 to 1994. This relation between return and yield is robust to various specifications of multifactor asset pricing models that incorporate the Fama–French factors. The magnitude of the yield effect is too large to be explained by a “tax penalty” on dividend income and is not explained by previously documented anomalies. Interestingly, the effect is primarily driven by smaller market capitalization stocks and zero‐yield stocks.